Perilaku Beton Porous Dengan Penambahan Zat Aditif Superplastizer (Sika Viscocrete) - Ghozi, Mohammad; Budiati, Anik; Yamil Aziz, Haitsam (INTER TECH, 2024)
ABSTRACT According to ACI 522R-10, Larvious Concrete, or Pervious Concrete is defined as concrete that has a slump value almost close to zero, which is formed from Portland cement, coarse aggregate, a little or No. fine aggregate, admixture, and water. Potons concrete (Previous concrete) is an environmentally friendly concrete that has cavities andi s returnable, so it can allow water to flow trough the cavities formed. Porous concrete is composed of coarse is composed of coarse aggregate covered with a thin layer of cement paste of around 1,3 mm. This research compares the compressive strength values of peggyz concrete, and the porosity of normal concrete with a mixture of Sika Viscocrete additives with compositions of 0,5%, 1%, 1,5%, and 2% based on the ASTM C1754-12 method in SKh- 1.5.14 Porous Concrete, The results of the research showed the average compressive strength of normal porous concrete at 7 days was 3,22 MPa, 3,14 MPa at 14 days, 3,39 MPa at 21 days and 4,28 MPa at 28 days. Meanwhile, the highest compressive strength of porous concrete wa at a percentage of 0,5% at 28 days with a value of 3,69 MPa. For the normal concrete porosity test value, it was found to be 14,12%, while 0,5%  additive was 12,29 MPa, 1% additive was 12,76 MPa, 1,5% was 12,45 MPa and 2% additive was 11,9%. From this research, there are 4 variants of adding Sika Viscocrete additives to the weight of the cement composition, namely 0,5%, 1%, 1,5%, and 2% with a sample size of 3 samples for each variant. Material testing methods and calculating the compressive strength of normal porous concrete with the addition of mixture of additives obtained the average compressive strength and also the prosity value of porous concrete. Keywords : Normal Porous Concrete, Additives, Concrete Compressiive Strength ABSTRAK Menurut ACI 522R-10, Beton Porous didefinisikan sebagai beton yang memiliki nilai slump hampir mendekati nol, yang terbentuk dari semen Portland, agregat kasar, sedikit agregat halus atau tidak sama sekali, campuran tambahan (admixture), dan air. Beton porous (pervious concrete) merupakan beton ramah lingkungan yang mempunyai rongga dan bersifat permeabilitas, sehingga dapat  memungkinkan mengalirkan air melaui rongga yang terbentuk. Beton porous terususun atas agregat kasar yang diselimuti dengan lapisan pasta semen tipis sekitar 1,3 mm.  Penelitian ini membandingkan nilai kuat tekan beton porous dan porositas beton normal dengan campuran zat aditif Sika Viscocrete dengan komposisi 0,5%, 1%, 1,5%, dan 2% yang didasarkan pada metode ASTM C1754-12 pada SKh-1.5.14 Beton Porous. Hasil penelitian didapatkan rata-rata kuat tekan beton porous normal pada umur 7 hari sebesar 3,22 MPa, umur 14 hari sebesar 3,14 MPa, umur 21 hari 3,39 MPa dan umur 28 hari 4,48 MPa. Sedangkan kuat tekan teringgi beton porous pada  prosentase 0,5 % pada umur 28 hari dengan nilai 3,69 MPa. Untuk nilai pengujian porositas beton normal didapatkan 14,12% sedangkan 0,5% zat aditif sebesar 12,29 Mpa, 1% zat aditif sebesar 12,76%, 1,5% zat aditif sebesar 12,45 Mpa dan 2% zat aditif 11,9 %. Dari penelitian ini, terdapat 4 varian penambahan zat aditif Sika Viscocrete terhadap berat komposisi semen yaitu, 0,5%, 1%, 1,5% dan 2% dengan jumlah sampel masing- masing varian  sebanyak 3 benda uji. Metode pengujian material dan perhitungan kuat tekan beton porous normal dengan penambahan campuran zat aditif didapatkan kuat tekan rata- rata dan juga nilai porositas pada beton porous. Kata Kunci : Beton porous normal, Zat aditif, Kuat Tekan beton